ANALYSIS OF THE ROLE OF THE POLICE IN LAW ENFORCEMENT AGAINST TERRORISM CRIMINAL ACTS - Muhammad Ishaq Alkays; Sudarto; Sujono (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
Terrorism is an extraordinary crime that threatens national security, public safety, and the rule of law. The Poso region in Central Sulawesi has long been exposed to terrorist activities, particularly by the East Indonesia Mujahideen (MIT) group. In addressing this threat, the Indonesian National Police (Polri), through the Special Detachment 88 Anti-Terrorism Unit (Densus 88 AT), plays a crucial role in enforcing anti-terrorism laws. This study aims to analyze the law enforcement efforts carried out by Densus 88 AT in handling terrorism cases involving wanted persons (DPO) in Poso, as well as to examine the challenges faced from legal and human rights perspectives. The research applies a normative-empirical approach by combining statutory analysis, conceptual frameworks, and case studies, supported by primary, secondary, and tertiary legal materials. The findings indicate that Indonesia has a strong legal framework for combating terrorism, particularly through Law Number 5 of 2018. Law enforcement efforts in Poso have been effective in enhancing security, as demonstrated by the successful neutralization of key terrorist actors. However, several challenges remain, including issues related to the criminal justice process, human rights protection, limited public participation, and coordination among institutions. In practice, obstacles are categorized into structural, substantive, and cultural aspects. Structural challenges include difficult geographical conditions and inter-agency coordination. Substantive issues involve debates over the use of force under special legal authority. Cultural barriers, such as low public trust, also hinder early detection and prevention. Therefore, counter-terrorism law enforcement must balance security, justice, legal certainty, and human rights to ensure effective and fair outcomes.